Supramolecular Hydrogel with Orthogonally Responsive R/G/B Fluorophores Enables Multi‐Color Switchable Biomimetic Soft Skins. (18th November 2021) - Liu, Hao; Wei, Shuxin; Qiu, Huiyu; Si, Muqing; Lin, Guoqing; Lei, Zhenkuang; Lu, Wei; Zhou, Lei; Chen, Tao
Abstract: Many living creatures have evolved to show diverse appearance color changes in response to multiple environmental stimuli for attraction, warning, or disguise in their environments. However, it is challenging to construct artificial soft polymer hydrogels with similar multi‐responsive multicolor tunable behaviors, but such materials can serve as soft biomimetic skins to dramatically enhance the function of certain machines. Herein, a specially designed material structure to present an innovative class of supramolecular fluorescent polymeric hydrogels with the integrated properties of wide multi‐color tunability, multi‐responsiveness, self‐healing, and remolding capacities is proposed. A key feature of this rational hydrogel design is that multiple fluorophores (blue (B) aggregation‐induced emissive and red/green (R/G) lanthanide coordinated ones) are organized separately into different polymer chains of one single supramolecular polymer network. Consequently, the B and R/G fluorophores are engineered to be orthogonally responsive, and the fluorescence intensity of each fluorophore can be controlled independently by different external stimuli, which contribute to multi‐responsive multicolor fluorescence response. Besides, the hydrogels also have satisfying self‐healing and remolding capacities. All of these promising advantages together further enabled the construction of soft biomimetic color‐changing skins that can help the existing robots achieve the desirable camouflaging function. Abstract : An innovative class of supramolecular fluorescent hydrogels is fabricated by organizing orthogonally responsive R/G/B luminogens into different polymer chains of a dynamic polymer network with the integrated multi‐color tunable, multi‐responsive, self‐healing, and remolding properties. Based on this multifunctional synergy, conformal biomimetic soft skins that can help the existing robots achieve the camouflaging function are demonstrated.